The Six A’s: Challenges of Primary Health Care in Federalism in Nepal - Mahato, Anrud Kumar; Dash, Mamata; Mehta, Manisha Kumari; Chaudhary, Nirajan; Joshi, Pooja; Sah, Bandana; Bogati, Mina; Mahato, Mina; Joshi, Prekshya; Yadav, Januka; Bhandari, Sirjana; Dulal, Bina; et al. (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
No abstract available.